Teachers’ written school memories and the change to the comprehensive school system in Finland in the 1970s - Marjo Nieminen (Routledge, 2026)
This paper focuses on teachers’ written memories of Finland’s comprehensive school reform in the 1970s and examines teachers’ reminiscences of this major change, when elementary (primary) schools and lower secondary (grammar) schools were transformed into comprehensive schools, thereby guaranteeing nine-year basic education with a unified curriculum for all pupils. The teachers’ written memories are part of the larger national collection of school memories arranged in 2013 by two academic societies. This study’s focus lies in these teachers’ highly sensitive, grass-roots level personal perspectives. The teachers’ narratives comprised vivid and concrete memories in which they recalled the past nostalgically and in detail. In the reminiscences, the change in the education system was noted and even analysed in a versatile way, but at the same time, the reform was viewed as merely one episode occurring during these teachers’ individual life paths. The writers emphasised the reform’s positive aspects and did not interpret contradictions as overwhelming, although some narratives included reminiscences in which the disputes from that period were crystallised. The collective narrative in the accounts transformed from uncertainty and contradictions at the beginning of the comprehensive school reform to favourableness and positive attitudes toward the new education system after the transition period.